مفسرین ِ اندلس کےمقدمات میں مباحثِ قراءاتِ قرآنیہ : ایک تجزیاتی مطالعہ (Al-Qamar, 2022)
Al-Andalus or Spain experienced the heights of knowledge and sciences under the magnificent Muslim rule for almost eight centuries. Most of the Iberian Peninsula was marked with learning and development due to remarkable Muslim dynasties. Muslims achieved great glory in Andalus not only in terms of lands but in sciences. Quranic sciences including Tafsir (exegesis) and Qira’at (Quranic readings) are worth mentioning among these bits of knowledge. Andalusian commentators wrote great Tafthirs that later paved the way for more research.  The discussions related to Qira’at (Quranic readings) are found in the exegesis of commentators of Andalus such as ‘Tafsir-ul-Muharrar ul Wajeez’ by Ibne Attiya, ‘Al Jamia Li Ahkam ul Quran’ by Qurtubi, Kitab ul Mubani, Kitab-ul-Tas’heel Li Ulum Tanzeel by Alama Ibn-e-Jozi and Al-Bahr-ul-Muheet by Abu Hayyan Al-Andalusi. This paper aims to highlight some Andalusian exegesis to reflect on Muslim commentators' views on Qira'at. By applying the qualitative method, this research article will provide an analytical study of Ilm-ul-Qira’at (the science of Quranic Readings) in the exordiums of Andalusians commentators.
Keywords: Andalus; Qira’at; Commentators; Quran; exordium